Photocatalytic Degradation of Reactive Yellow Dye in Wastewater using H2O2/TiO2/UV Technique - Mohammed, Noor A.; Alwared, Abeer I.; Salman, Mohammed S. (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
In the present study, advanced oxidation treatment, the TiO2 /UV/H2O2 process was applied to decolorisation of the reactive yellow dyes in aqueous solution. The UV radiation was carried out with a 6 W low-pressure mercury lamp. The rate of color removal was studied by measuring the absorbency at a characteristic wavelength. The effects of H2O2 dosage, dye initial concentration and pH on decolorisation kinetics in the batch photoreactor were investigated. The highest decolorisation rates were observed (98.8) at pH range between 3 and 7. The optimal levels of H2O2 needed for the process were examined. It appears that high levels of H2O2 could reduce decolorisation by scavenging the *OH. The color degradation rate decreases as the dye concentration increases. The rate coefficient (k=0.0319 min-1) of degradation, follows the pseudo-first-order kinetics.